Constrained Galerkin variational integrators and modified constrained symplectic Runge-Kutta methods - Wenger, Theresa; Ober-Blöbaum, Sina; Leyendecker, Sigrid (Proceedings of the International Conference of Numerical Analysis and Applied Mathematics (ICNAAM), 2016)
The presented constrained Galerkin variational integrators base on the higher order variational integrators in [1], now applied to holonomically constrained systems and are an extension of the constrained Galerkin methods in [2]. Sufficient conditions are given to obtain a stiffly accurate integration scheme, its structure preserving properties are analysed and the convergence order as well as the computational efficiency are investigated numerically. The equivalence to constrained symplectic Runge-Kutta methods is shown, with focus on a modified constrained symplectic Runge-Kutta method, that was first introduced in [3], there for the unconstrained cas